Time of metastatic disease presentation and volume of disease are prognostic for metastatic hormone sensitive prostate cancer (mHSPC) - Francini, Edoardo; Gray, Kathryn P.; Xie, Wanling; Shaw, Grace K.; Valença, Loana; Bernard, Brandon; Albiges, Laurence; Harshman, Lauren C.; Kantoff, Philip W.; Taplin, Mary‐Ellen; Sweeney, Cristopher J. (The Prostate, 2018)
Background Currently, there is no universally accepted prognostic classification for patients (pts) with metastatic hormone sensitive prostate cancer (mHSPC) treated with androgen deprivation therapy (ADT). Subgroup analyses demonstrated that pts with low volume (LV), per CHAARTED trial definition, mHSPC, and those who relapse after prior local therapy (PLT) have longer overall survival (OS) compared to high volume (HV) and de‐novo (DN), respectively. Using a hospital‐based registry, we aimed to assess whether a classification based on time of metastatic disease (PLT vs DN) and disease volume (LV vs HV) are prognostic for mHSPC pts treated with ADT. Methods A retrospective cohort of consecutive patients with mHSPC treated with ADT between 1990 and 2013 was selected from the prospectively collected Dana‐Farber Cancer Institute database and categorized as DN or PLT and HV or LV, at time of ADT start. Primary and secondary endpoints were OS and time to castration‐resistant prostate cancer (CRPC), respectively, which were measured from date of ADT start using Kaplan‐Meier method. Multivariable Cox proportional hazards models using known prognostic factors was used. Results The analytical cohort consisted of 436 patients. The median OS and time to CRPC for PLT/LV were 92.4 (95%CI: 80.4‐127.2) and 25.6 (95%CI: 21‐35.7) months and 43.2 (95%CI: 37.2‐56.4) and 12.2 (95%CI: 9.8‐14.8) months for DN/HV, respectively, whereas intermediate values were observed for PLT/HV and DN/LV. A robust gradient for both outcomes was observed (Trend test P < 0.0001) in the four groups. In a multivariable analysis, DN presentation, HV, and cancer‐related pain were independent prognostic factors. Conclusions In our hospital‐based registry, time of metastatic presentation and disease volume were prognostic for mHSPC pts treated with ADT. This simple prognostic classification system can aid patient counseling and future trial design.